2014
DOI: 10.3390/ijms15033784
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Acetylcholinesterase Modulates NMDA Receptor Antagonist Mediated Alterations in the Developing Brain

Abstract: Exposure to N-methyl-d-aspartate (NMDA) receptor antagonists has been demonstrated to induce neurodegeneration in newborn rats. However, in clinical practice the use of NMDA receptor antagonists as anesthetics and sedatives cannot always be avoided. The present study investigated the effect of the indirect cholinergic agonist physostigmine on neurotrophin expression and the extracellular matrix during NMDA receptor antagonist induced injury to the immature rat brain. The aim was to investigate matrix metallopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Similarly, a previous study showed that the enzymatic activity of MMP2 increased after treatment with the non-competitive NMDA receptor antagonist MK801 in newborn rats. 39 analysis in the latter study. 39 Taken together, the ketamine-induced laminin degradation observed in our study may be due to the enhanced activity of MMP9.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Similarly, a previous study showed that the enzymatic activity of MMP2 increased after treatment with the non-competitive NMDA receptor antagonist MK801 in newborn rats. 39 analysis in the latter study. 39 Taken together, the ketamine-induced laminin degradation observed in our study may be due to the enhanced activity of MMP9.…”
Section: Discussionmentioning
confidence: 60%
“…39 analysis in the latter study. 39 Taken together, the ketamine-induced laminin degradation observed in our study may be due to the enhanced activity of MMP9.…”
Section: Discussionmentioning
confidence: 60%
“…An important finding that gives support is that cells with increased AChE activity can easily switch to an apoptotic state by caspases cleavage [68]. Another important fact of its involvement with cellular death processes is that AChE inhibitors in pathological state slow down neurodegeneration by increasing BDNF levels [35]. In the present study, we found an increase in AChE activity and decrease of its immunocontent in cerebellum.…”
Section: Discussionmentioning
confidence: 68%
“…It has been shown that in the hippocampus, BDNF production is directly influenced by acetylcholine levels [33]. In this context, several studies have shown that acetylcholinesterase (AChE) inhibition increases BDNF levels by prolonging acetylcholine action on its receptors [34,35]. The crosstalk between the cholinergic system and BDNF production suggests an important role of the cholinergic system in cell survival [36].…”
Section: Introductionmentioning
confidence: 98%
“…Many previous studies have reported that BDNF may confer protective effects against various neurotoxic conditions in the brain, via reduction of the AChE levels or activity [6466]. In addition, emerging evidence suggests that regulation of AChE activity by BDNF is related to hippocampal neurogenesis [61, 6769]. For example, huperzine A, an AChE inhibitor, increases BDNF mRNA and protein levels, while cholinergic denervation or muscarinic antagonist treatment, such as atropine, decreases the hippocampal BDNF mRNA levels [70].…”
Section: Discussionmentioning
confidence: 99%